The Effect of Applying Actional Functional Model (AFM) on The Student’s Achievement in Speaking - Anni Alvionita Simajuntak; Annisa Risma Lubis; Della Fransiska Ginting (English Language Teaching and Research, 2018)
This study was aimed at describing The Effect of Applying Actional Functional Model (AFM) on the Students’ Achievement in Speaking at the tenth grade of SMAS Nurul Islam Indonesia Medan in academic year 2013-2014. . The population was 40 students and the sample of this research were 40 students too. This research was conducted by the experimental research.The technique of analyzing data of this study was applied by using quantitative data.The quantitative data were taken from the writing test. Most of the students achieved a good score at the test.The passing grade of English lesson was 70.It shows that the students at the second class of SMA Nurul Islam Indonesia Medan who were taught by using AFM could learning speaking effectively, than those were taught by using conventional. The student who were taught learning speaking by using AFM got 93% higher scores than those who taught without AFM.The null conventional method was rejected and alternative hypothesis was accepted. It means that there was significant effect of using AFM.The result of the data analysis that the mean of the experimental was 93%Keyword: The Students’ Achievement, Speaking, Actional Functional Model (AFM)